Integrative physiological, transcriptomic, and metabolomic analysis of Abelmoschus manihot in response to Cd toxicity - Wu, Mengxi; Xu, Qian; Tang, Tingting; Li, Xia; Pan, Yuanzhi (Frontiers in Plant Science, 2024)
Rapid industrialization and urbanization have caused severe soil contamination with cadmium (Cd) necessitating effective remediation strategies. Phytoremediation is a widely adopted technology for remediating Cd-contaminated soil. Previous studies have shown that Abelmoschus manihot has a high Cd accumulation capacity and tolerance indicating its potential for Cd soil remediation. However, the mechanisms underlying its response to Cd stress remain unclear. In this study, physiological, transcriptomic, and metabolomic analyses were conducted to explore the response of A. manihot roots to Cd stress at different time points. The results revealed that Cd stress significantly increased malondialdehyde (MDA) levels in A. manihot, which simultaneously activated its antioxidant defense system, enhancing the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) by 19.73%–50%, 22.87%–38.89%, and 32.31%–45.40% at 12 h, 36 h, 72 h, and 7 days, respectively, compared with those in the control (CK). Moreover, transcriptomic and metabolomic analyses revealed 245, 5,708, 9,834, and 2,323 differentially expressed genes (DEGs), along with 66, 62, 156, and 90 differentially expressed metabolites (DEMs) at 12 h, 36 h, 72 h, and 7 days, respectively. Through weighted gene coexpression network analysis (WGCNA) of physiological indicators and transcript expression, eight hub genes involved in phenylpropanoid biosynthesis, signal transduction, and metal transport were identified. In addition, integrative analyses of metabolomic and transcriptomic data highlighted the activation of lipid metabolism and phenylpropanoid biosynthesis pathways under Cd stress suggesting that these pathways play crucial roles in the detoxification process and in enhancing Cd tolerance in A. manihot. This comprehensive study provides detailed insights into the response mechanisms of A. manihot to Cd toxicity.